2021
DOI: 10.3390/ijerph18168742
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Increases the Risk of Mortality among Patients with Colorectal Cancer: A Nationwide Population-Based Retrospective Cohort Study

Abstract: Background: Colorectal cancer (CRC) is the third leading cause of cancer-related deaths in Taiwan. Chronic obstructive pulmonary disease (COPD) is associated with CRC mortality in several population-based studies. However, this effect of COPD on CRC shows no difference in some studies and remains unclear in Taiwan’s population. Methods: We conducted a retrospective cohort study using Taiwan’s nationwide database. Patients newly diagnosed with CRC were identified from 2007 to 2012 via the Taiwan Cancer Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition to the impact on cancer incidence, poorer survival and lower quality of life also result from the presence of concomitant pulmonary diseases in patients burdened with lung, laryngeal, and colorectal cancers 138 , 139 , 140 . Such phenomena could be partially explained by the fact that the existence of pulmonary comorbidities has extensively affected the prognosis and complicated the management and treatment of cancer patients with comorbid conditions.…”
Section: Pre-existing Diseases With Reciprocal Influence On Chemotherapymentioning
confidence: 99%
“…In addition to the impact on cancer incidence, poorer survival and lower quality of life also result from the presence of concomitant pulmonary diseases in patients burdened with lung, laryngeal, and colorectal cancers 138 , 139 , 140 . Such phenomena could be partially explained by the fact that the existence of pulmonary comorbidities has extensively affected the prognosis and complicated the management and treatment of cancer patients with comorbid conditions.…”
Section: Pre-existing Diseases With Reciprocal Influence On Chemotherapymentioning
confidence: 99%
“…Few studies have investigated the relationship between preoperative pulmonary function and short-and long-term outcomes in patients who underwent abdominal surgeries for GC and colorectal cancer. [18][19][20][21][22][23] This study aimed to test the hypothesis that preoperative pulmonary function is related to short-and long-term outcomes in patients who underwent gastrectomy for GC.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has unveiled correlations between the progression or mortality of COPD and CRC. One nationwide retrospective cohort study revealed that CRC patients with COPD had an increased risk of mortality [ 8 ]. Additionally, a prospective follow-up investigation of CRC patients demonstrated significant associations between COPD and comorbidities such as diabetes and cardiocerebrovascular disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%